Stratigraphic revision and lithofacies of La Silla Formation (Lower Ordovician) in the eastern Precordillera of San Juan, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Cambro-Ordovician carbonate platform succession of the Precordillera Oriental of western Argentina is some 2000 m thick and consists of five formations, from base to top, La Laja, Zonda, La Flecha, La Silla and San Juan (Keller, 1999; Bordonaro, 2003). La Silla Formation (latest Cambrian-Early Ordovician) was defined by Keller et al. (1994) from the lower part of the San Juan Formation. It reaches some 350 m in thickness and consists of a distinctive succession of dominantly light-coloured, poorly fossiliferous limestones.The upper part of La Silla Formation is extensively quarried because of the remarkable purity of the limestones. Based on a detailed study of the type section in the northern outcrop area near Jáchal and seven sections in the southern area near San Juan (Fig. 1a), we propose a formal stratigraphic subdivision of La Silla Formation into three members. These are, from base to top, the Río del Agua Member, Río Blanco Member and Río Salado Member (Fig. 1b), which are 85, 140 and 81 m in their respective type sections. This subdivision is based in the preferential occurrence of creamcoloured dolostones interbedded in the middle part of the formation, whereas the lower and upper members are essentially monotonous limestones. Keller (1999) erected an informal tripartite subdivision conforming to three putative, shallowing-upward sequences, with the boundaries recording abrupt changes in relative sealevel. We do not detect this pattern and our proposed members do not coincide with this subdivision.We recognize nine individual lithofacies types (Fig. 2a-f). These are for the most part similar to those determined by Keller (1999) and Cañas (1999), but we consider that they over-estimated the abundance of muddy facies in the form of lime mudstone, wackestone and packstone. Limestones in all three members are dominantly thick- and massively bedded peloidal grainstones exhibiting tabular and gently undulating bedding. In the lower and upper members there are subordinate ooidal grainstones, along with rare peloidal packstone, intraclastic rudstone, mudstone, microbial laminites and thrombolite patch reefs. Dolostones are of two types: thick- and massively bedded and commonly cherty, and medium beds that are plane- and cross-laminated. The former is the dolomitized equivalent of the peloidal grainstone. The latter often occurs with thin intraclastic rudstones and represents relatively coarse grainstones that were preferentially dolomitized. These dolomites preserve evidence of unidirectional and oscillating currents.Our eight measured sections indicate that there was varying amounts of subsidence across the carbonate platform (Fig. 3), although precise correlation is impossible owing to the lack of biostratigraphic data. La Silla Formation represents a distinct phase in the Cambro-Ordovician evolution of the eastern Precordillera, with mainly lower energy peritidal limestones of La Flecha Formation below and open-shelf, fossiliferous muddy limestones of the (emended) San Juan Formation above. The dominance of peloidal grainstone suggests an open-shelf setting as well but one characterized by virtually continuous low-level turbulence yet absence of extreme events like major storms that would have formed deep scours and high-relief bedforms. While scoured surfaces do occur sporadically in the Río Blanco Member, large bedforms are not present in La Silla Formation (Fig. 4a-e).
Keywords: Stratigraphic nomenclature; Carbonates; Lower Ordovician; La Silla Formation; Eastern Precordillera.